When the Red Light Speaks: Sociotechnical Controversies, Spatial Justice, and Temporal Democracy at the Samsat - Kiaracondong Intersection, Bandung - Farenza Fadil Muhaji; Edit Rahmadhita Anas; Tia Muhamad Reza; Tri Nugroho Putro; Yusran Kahfi Ahmar (Jurnal Locus Penelitian dan Pengabdian, 2026)
The Samsat - Kiaracondong (Kircon) intersection in Bandung, Indonesia, reportedly features the longest red-light waiting cycle in the country, reaching peak durations of over 720 seconds. While technocratic discourse frames this signal as a neutral tool for traffic optimization, this article argues that it functions as a contested sociotechnical node where questions of spatial and temporal justice are continuously negotiated. Drawing on Actor-Network Theory (ANT), particularly Latour's concepts of "matters of concern" and the tracing of associations, the study analyzes four layers of sociotechnical controversy: group formation, the distributed nature of action, the agency of non-human objects, and the construction of truth. Using qualitative secondary data including digital media, institutional documents, and social media discourse the analysis reveals that the intersection generates multiple, often conflicting social groups (e.g., victimized motorists, rule-breakers, informal economy actors, marginalized pedestrians), each constituted through its specific relationship to the signal's temporal rhythm. Action at the intersection is distributed across a heterogeneous network of human and non-human actants, including traffic officers, algorithmic control systems, and CCTV infrastructure. The study further demonstrates how technocratic truth claims are contested by citizen counter-discourses rooted in lived experience. The findings contribute to urban ANT scholarship, mobility justice studies, and infrastructure governance in the Global South by showing that even mundane technical artifacts are sites of vernacular democracy, where competing claims to time and space are enacted daily. The article concludes by calling for more inclusive, democratic approaches to urban infrastructure governance that acknowledge the multiplicity of legitimate interests at stake.